Description of five new species from southern China, with note on the type species of Latouchia Pocock, 1901 (Araneae, Halonoproctidae) - Long Hao; Kun Yu; Feng Zhang (Biodiversity Data Journal)
The genus Latouchia Pocock, 1901 previously included 25 known species and one subspecies from Asia, 12 species and one subspecies were reported in China.Five new species of Latouchia Pocock, 1901 from southern China are described: L. calcicola sp. nov. (♂♀) from Hainan, L. jinyun sp. nov. (♂♀) from Chongqing, L. linmufu sp. nov. (♂♀) from Hunan, L. wenchuan sp. nov. (♂) from Sichuan and L. yaoi sp. nov. (♂♀) from south part of Shaanxi. DNA barcodes of the new species described herein are provided. The potential error in the previous illustrations of the alleged male of L. fossoria Pocock, 1901 (type species of the genus) is pointed out.